Validation Of Spectrophotometry-Visble Method On The Determination Of Borax Levels In Meatballs - Sudjarwo Sudjarwo; Poedjiarti S; Angerina N (Universitas Airlangga, 2021)
Borax, in illictic additive substance, is added on certain food product as a e preservative and rubbery. Therefore, the determination of borax in the food product such as meatball is very impotant in view of meatball is a food product often consumed by community. Vis- Spectrophotometric method with curcumine 0.125% as a reagent and glacial acetic acid-sulphuric acid has been used for determination of borax in this research. Curcumin reagent was selected because sensitivity of the method and the reproducibility of the results are affected by quality of the reagent other than rigorous observance of the reaction conditions (temperature, time, reagent quantities). Glacial acetic acid- sulphuric acid was used to create acid condition, so that curcumin and boron form a violetred 2:1 complex called rosocyanin. The optimum result was obtained when 1/. ml solution of 0.125% curcuumin and 1.0 ml concentrated sulphuric acid were added and the absorbance was measured after 70 minutes at 547 nm. The results showed linear regression y = 1.3127x – 0.0994, r = 0.9690 > r table (n = 5) is 0.878 and p = 0.007 (p< 0.01) and Vxo is was 15,53%. The detection limit and quantitation limit were 9.7.10-4 ppm and 2.94. 10-3 ppm respectively. The recovery and coefficient variation were 47.56%±3,92%. Determination of borax in three meatball samples which were taken from a location in Surabaya showed that the sample contained borax with concentration of 0.0205; 0.0151; 0.0210 (% w/w) respectively.